(untitled) (The Review of Diabetic Studies, 2024)
Background: Healthcare‑associated infections (HAIs) represent a major global threat, contributing to significant morbidity, mortality, prolonged hospitalization, and economic burden. Their development is influenced by invasive procedures, indwelling devices, antimicrobial resistance, and complex interactions between pathogens, host susceptibility, and the healthcare environment. Aim: To synthesize multidisciplinary perspectives on the etiology, epidemiology, pathophysiology, evaluation, and management of HAIs, emphasizing the essential roles of clinical, diagnostic, and preventive strategies in reducing infection rates. Methods: This review integrates evidence across healthcare disciplines—nursing, epidemiology, radiology, laboratory diagnostics, pharmacy, and physical therapy—drawing from contemporary data on pathogen patterns, risk factors, transmission routes, diagnostic approaches, and best‑practice prevention protocols. Results: Pneumonia, surgical site infections, bloodstream infections, gastrointestinal infections, and urinary tract infections constitute the most common HAIs, with multidrug‑resistant organisms significantly complicating treatment. Device‑associated infections such as CLABSI, CAUTI, and VAP arise primarily from biofilm formation and breaches in aseptic technique. Effective diagnosis relies on targeted cultures, imaging, and pathogen‑specific testing. Management requires prompt antimicrobial therapy, source control, device reassessment, and stewardship‑guided de‑escalation. Prevention strategies—including hand hygiene, environmental cleaning, isolation precautions, and multidisciplinary collaboration—can prevent over half of major HAIs. Conclusion: HAIs remain a preventable yet persistent healthcare challenge. Multidisciplinary coordination, adherence to evidence‑based infection control, and robust antimicrobial stewardship are essential to reducing incidence, improving outcomes, and decreasing healthcare costs.